Vitamin D and bone mineral density status among postmenopausal Bangladeshi women (IMC Journal of Medical Science, 2019)
Background and objectives: Low vitamin D is a global problem in all age groups as is osteoporosis in postmenopausal women. The present study was carried out in an urban hospital to assess serum 25-hydroxyvitamin D [25(OH)D] level and bone mineral density (BMD) in postmenopausal women (PMW) and to evaluate correlation between serum 25(OH)D levels and BMD.Methods: A single center cross-sectional study was conducted among 133 apparently healthy PMW aged 45 years and above with the history of complete cessation of menstruation over a period of more than 1 year. Serum 25(OH)D, BMD and serum intact parathyroid hormone (iPTH) were determined. Patients having both vitamin D and BMD values were analyzed for correlations. Similarly, correlation of vitamin D, iPTH and BMD were determined.Results: Among the study population, 63 (47.4%) had deficient (